Deceleration of the electron transfer reaction in the photosynthetic reaction centre as a manifestation of its structure fluctuations - Kharkyanen, V.N.; Barabash, Yu.M.; Berezetskaya, N.M.; Olenchuk, M.V.; Knox, P.P.; Christophorov, L.N. (Вiopolymers and Cell, 2010)
Aim. To extract information on the nature of protein structural relaxation from the kinetics of electron transfer reaction in the photosynthetic reaction centre (RC). Methods. The kinetic curves obtained by absorption spectroscopy are processed by a maximum entropy method to get the spectrum of relaxation times. Results. A series of distinctive peaks of this spectrum in the interval from 0.1 s to hundreds of seconds is revealed. With the time of exposure of the sample to actinic light increasing, the positions of the peak maxima grow linearly. Conclusions. Theoretical analysis of these results reveals the formation of several structural states of the RC protein. Remarkably, in each of these states the slow reaction kinetics follow the same fractional power law that reflects the glass-like properties of the protein. Цель. Определить характер структурной релаксации белка из анализа кинетики реакции электрон- ного транспорта в фотосинтетическом реакционном центре (РЦ). Методы. Кинетические кривые, полученные методами абсорбционной спектроскопии, обрабатывали с использованием метода максимальной энтропии для получения спектра времен релаксации. Результаты. Обнаружен ряд характерных пиков этого спектра в интервале от 0,1 до сотен секунд. С увеличением длительности экспозиции образца в актиничном свете положения максимумов пиков линейно возрастают. Выводы. Из теоретического анализа результатов следует, что появляется несколько структурных состояний белкового компонента РЦ, в которых, однако, медленная кинетика реакции подчиняется одному и тому же дробно-степенному закону, отражающему стеклоподобные свойства белка. Мета. Визначити характер структурної релаксації білка з аналізу кінетики реакції електронного транспорту у фотосинтетичному реакційному центрі (РЦ). Методи. Кінетичні криві, одержані з використанням абсорбційної спектроскопії, обробляли методом максимальної ентропії для отримання спектра часів релаксації. Результати. Знайдено низку характерних піків цього спектра в интервалі від 0,1 до сотень секунд. Зі збільшенням тривалості експозиції зразка в актинічному світлі положення максимумів піків лінійно зростають. Висновки. З теоретичного аналізу результатів випливає, що виникає декілька структурних станів білкового компонента РЦ, у яких, однак, повільна кінетика реакції підпорядкована одному й тому ж дрiбно-ступеневому закону, що відбиває склоподібні властивості білка.